Modern Methods of Urban Energy System Planning - Т. M. Bugaeva; O. V. Novikova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Knowledge of the nature of the energy load alterations not only in time, but also in space will allow achieving the optimal structure of energy sources in the city and thereby reducing unproductive energy costs of energy resources and increasing energy efficiency. Changing the paradigm of power supply systems development towards the development of small distributed power production, intellectualization and demand management requires a more accurate understanding of the planned local loads in the city. At present it is still difficult to obtain such data; it requires analysis of many sources and, consequently, takes a lot of time. The article presents a possible algorithm of formation of the space-time profile of energy resources consumption. At the heart of the load disaggregation there is a spatial distribution of consumers in the city, estimated by the density of the distribution area of buildings of energy consumer groups. The dimension of the model is not limited in both temporal and spatial resolution: the model is flexible and can be adapted to different cases and local conditions. The proposed algorithm has been applied to the modeling of the profile of electricity consumption in St. Petersburg. The profile is based on an annual graph of electricity consumption by hour (8760 values). The spatial resolution of the model ranges from hundreds of meters to several kilometers and depends only on the availability of initial data. In the example, the division of the city territory into administrative districts (18 districts of St. Petersburg) is used as a spatial unit. The obtained results showed their logicality and compliance with empirical observations.